„Zjednoczeni dla Śląska” - Upper-Silesians support for regional initiative - Muś, Anna (Political Preferences, 2017)
Upper Silesia region is recognised as particular due to the forms of social and political behaviour of part of its residents. Upper-Silesians, as ethnic group having strong conviction about their separateness, build political affiliation based on the conflict centre – periphery, at least to some extent. This is certainly true for protagonist of Silesian regional movement, but this article deals with the problem whether voters act similarly. Moreover the article study to some extend the possibility of creation of ethnoregionalist party in the future and what kind of consequences this may have on the politics in the region. Key words: regionalist party, ethnoregionalist party, proto-party, Upper Silesians, Upper Silesia